Adoption status of good agricultural practices among vegetable growers in the Arghakhanchi district of Nepal - Nepal , Anish; Khanal , Kapil; Parajuli , Nikita (Journal of Agriculture and Natural Resources, 2023)
The vegetable sector substantially contributes to the Nepalese economy and offers instant income, nutrition, and food security. The unsystematic use of agrochemicals for commercialising production has posed a threat to the sustainability of the vegetable sector in recent decades. The usage of agrochemicals in commercial vegetable production may be reduced by implementing Good Agriculture Practices (GAP). This study aims to find out the knowledge, application, and perception of farmers towards Good Agricultural Practices (GAP) along with the adoption index in the Arghakhanchi district of Nepal from February 2023 to June 2023. Altogether 125 households from Sandhikharka Municipality and Chhatradev Rural Municipality were chosen using stratified random sampling technique. Focus group discussion (FGD), Key Informant Interview (KII), and preliminary field visits were carried out to gather primary data, and a variety of literatures were reviewed to gather secondary data. The results showed that 38.4% of households (HHs) were aware of the GAP. The higher adopters were 15.48% HHs with a mean adoption value of 19.57. About15.4% HHs  were low adopters with an adoption value of 9.45 and 70.73% of HHs were medium adopters with an adoption value of 14.92 out of 29. The low level of GAP application was found in the harvesting method with the lowest mean score of 0.136, however, storage duration had the highest average score of 0.992. Farmers ranked insect pest damage as the most severe problem with an index value of 0.79, while weather as the least severe problem with an index value of 0.33 in rank I, and V respectively. All respondents gave their perception of GAP with 75.2% agree, 12.8% neither agree nor disagree and 12% strongly agree that GAP helps them to increase their productivity.